Survei Penggunaan Uji Statistik dalam Penelitian Tugas Akhir Mahasiswa dengan Topik Ergonomi di Prodi Teknik Industri Unika Atma Jaya Jakarta - ., Yanto (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2020)
This study presented a survey results of the statistical tools used by undergraduate university students in Department of Industrial Engineering,Faculty of Engineering, Atma Jaya Catholic University of Indonesia. A number of 26 reports of students’ final project from 2018-2020 was identified and studied. A checksheet form was developed to record the 14 statistical tools used by students consists of descriptive statistics (2 items), inference statistics (10 items), multivariate (1 item) and statistical package used (1 item). The data were analyzed for its frequency and percentage. Results showed that all reports used descriptive statistics to present participant’s demography of their research, as well as the summary of statistics. For inference statistics, the students used a variety of normality test, 2 t-test, anova, equal variance, proportion test, a few nonparametric tests, regression and correlation and multivariate statistics. For statistical package, most students used Minitab (46,2%), followed by SPSS (34,4%) and other such as AMOS, Listrel, PLS(15.4%). Among them, 11.5% used more than one software. In addition, the results of this study could be used to evaluate the contents of the relevant course.